1997
DOI: 10.1111/j.1651-2227.1997.tb08927.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dietary nucleotides on erythrocyte membrane fatty acids and plasma lipids in preterm infants

Abstract: These results do not suggest an effect of nucleotides on the red blood cell LC-PUFA profile in preterm infants. However, the nucleotides may increase the concentrations of triglycerides in plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
8
1
1
Order By: Relevance
“…Our trial showed that supplementation of infant formula with 33.5 mg/L (5 mg/100 kcal) free NT did not influence the FA status of term infants at 7 mon of age. Our results support the findings of Hernell and Lön-nerdal (14), Woltil et al (13), and Axelsson et al (12) but contrast with the frequently cited studies from Spain suggesting that dietary NT may play a role in enhancing enzymes involved in the conversion of 18-carbon PUFA precursors to their longer-chain derivatives (10,11,22). The Spanish studies report higher levels of LCPUFA in erythrocyte phospholipids, plasma lipids, and plasma phospholipids in the NT-supplemented group of infants compared with unsupplemented infants in the first months of life.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our trial showed that supplementation of infant formula with 33.5 mg/L (5 mg/100 kcal) free NT did not influence the FA status of term infants at 7 mon of age. Our results support the findings of Hernell and Lön-nerdal (14), Woltil et al (13), and Axelsson et al (12) but contrast with the frequently cited studies from Spain suggesting that dietary NT may play a role in enhancing enzymes involved in the conversion of 18-carbon PUFA precursors to their longer-chain derivatives (10,11,22). The Spanish studies report higher levels of LCPUFA in erythrocyte phospholipids, plasma lipids, and plasma phospholipids in the NT-supplemented group of infants compared with unsupplemented infants in the first months of life.…”
Section: Discussionsupporting
confidence: 95%
“…An area of controversy in NT nutrition relates to their ability to modulate the accumulation of long-chain PUFA (LCPUFA), such as DHA (22:6n-3) and arachidonic acid (20:4n-6) (10,11). Whereas reports from one laboratory suggest beneficial effects, subsequent studies involving preterm (12) or low-birth-weight infants (13) have been unable to confirm the LCPUFA-enhancing effects of supplemental NT compared with unsupplemented formula. In a more recent study designed primarily to examine the effect of added NT on iron status of term infants, there was also no significant difference between the NT-supplemented group and other formula groups in erythrocyte FA composition at both time points following commencement of feeding (4 and 6 mon of age) (14).…”
mentioning
confidence: 94%
“…Exogenous nucleotides are considered as conditional nutrients (Van Buren and Rudolph, 1997). Dietary nucleotides have beneficial effects upon small intestinal growth and development (Uauy, 1990; Iijima et al., 1993; Tanaka et al., 1996), lipid metabolism (Boza et al., 1992; Sato et al., 1995; Axelsson et al., 1997) and hepatic function (Lopez‐Navarro et al., 1996; Pérez et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Efetivamente, estes são considerados ingredientes funcionais com papel na síntese de DNA e RNA e provável ação imunológica, bem como no aumento da biodisponibilidade do ferro, na modificação favorável da microbiota intestinal e no metabolismo das lipoproteínas. [39][40][41][42][43][44] A suplementação com vitamina D durante o primeiro ano de vida, quer nos lactentes alimentados com leite materno quer nos que são alimentados com fórmulas infantis, reuniu consenso, o qual é concordante com as recomendações da Comissão de Nutrição da ESPGHAN. 45 Também houve consenso quanto à maior disponibilidade do cálcio no leite humano comparativamente às fórmulas infantis e à importância da relação Ca/P nestas para a otimização da sua absorção.…”
Section: Discussionunclassified